How does a preference-based generic health-related quality of life measure perform in patients with a rare disease? Measurement properties of the EQ-5D-Y proxy version among underage patients with neurofibromatosis type 1 - Wanxian Liang; Shihuan Cao; Yusi Suo; Lining Zhang; Lujia Yang; Hanfei Wang; Han Wang; Xuejing Jin (Orphanet Journal of Rare Diseases)
Abstract Background EQ-5D-Y is a pediatric preference-based health-related quality of life (HRQL) measure that is recommended in health economic evaluation according to China’s guidelines. However, there is limited evidence regarding how the EQ-5D-Y perform in patients with rare diseases in the country. Neurofibromatosis type 1 (NF1) is a rare disease that affects the growth and development of underage patients. This study aimed to examine the performance of EQ-5D-Y proxy version among underage NF1 patients in China. Methods Data from a nationwide cross-sectional survey from Nov 2022 to Jan 2023 was used. A total of 154 caregivers for underage NF1 patients who completed the EQ-5D-Y proxy version, PedsQL 4.0 Generic Core Scales (PedsQL GCS) proxy version, and Zarit Burden Interview (ZBI-22) were included. The performance of the EQ-5D-Y was assessed by response pattern (ceiling and floor effects), convergent validity against the PedsQL GCS, known-groups validity, and Shannon (H’) and Shannon evenness (J’) indices. Result Data from 154 caregivers were analyzed. The mean age of caregivers was 38.23 (6.02) years, and 78.57% of them were mothers of NF1 patients. The mean age of NF1 patients was 8.38 (3.34) years, with 51.30% being females. The ceiling effect of EQ-5D-Y was 30.52%, and floor effect was 0%. Moderate to strong correlations were found between EQ-5D-Y and PedsQL GCS dimensions that share similar constructs (rho − 0.42 to -0.60, all p values < 0.001). The hypotheses of known-groups defined by different PedsQL GCS and ZBI scores were validated. The EQ-5D-Y exhibited the strongest informativity and discriminatory power of the “feeling worried, sad or unhappy” dimension and weakest for the “mobility” dimension (H’(mobility) = 0.60, J’(mobility) = 0.38; H’(feeling worried, sad or unhappy) = 1.23, J’(feeling worried, sad or unhappy) = 0.78). Conclusions EQ-5D-Y is acceptable for measuring HRQL of underage NF1 patients in China. More evidence for using EQ-5D-Y in rare diseases is awaited.